Transformation of the ichthyological complex of the Sholokhove Reservoir (Bazavluk River): retrospective and current state - D. Kobyakov; О. Khristov; R. Novitskyi; O. Kolomiitseva (Ribogospodarsʹka Nauka Ukraïni)
Purpose. To assess the dynamics of changes in the state of the ichthyofauna of the Sholokhove Reservoir based on many years of ichthyological research (1966–2024).